Prevalence of musculoskeletal disorders among female workers in the fish processing industry in Odisha, India (International Journal of Occupational Safety and Health, 2025)
Introduction: The fish processing industry in India has experienced significant growth in recent years, making a substantial contribution to the national economy. Several tasks involved in processing are dependent on manual handling, which leads to the development of work-related musculoskeletal disorders (WMSDS). The study was made to assess the prevalence of WMSDs among the female fish processing workers.Methods: A total of 200 female workers were randomly selected from three fish processing units in Mancheswar  , Khurda district, Odisha. A descriptive design was chosen for the study, which involved assessing physical and demographic parameters, work organization, and work stress among female workers. A modified Nordic Questionnaire was used to assess pain and discomfort among the workers. The study also included posture analysis by using the Rapid Upper Limb Assessment (REBA) tool. The study was carried out for 10 months from February 2024 to November 2024.Results: 90% of the female fish processing workers complained of having discomfort in different parts of their bodies. The risk estimates also indicated that workers performing sorting were at 3.2 times (95% CI 2.0-5.1) at higher risk of developing pain and discomfort in the upper back, 10.2 times (95% CI 4.0-26.1) in the wrist and 3.8 times (95% CI 2.1-6.7) in the finger. The RULA score of posture practiced during sorting had a medium risk of MSD injury occurrence. Awkward posture increased the risk of MSD injury occurrence by 9.5 times (95% CI 2.2-11.3).Conclusion: The female workers of the fish processing industry experience pain and discomfort. Prolonged working in static, awkward, and standing postures, along with performing repetitive jobs, increases the risk of developing work-related MSDs.